2012
DOI: 10.1002/nbm.2827
|View full text |Cite
|
Sign up to set email alerts
|

A continuous‐flow, high‐throughput, high‐pressure parahydrogen converter for hyperpolarization in a clinical setting

Abstract: Pure parahydrogen (pH(2) ) is the prerequisite for optimal pH(2) -based hyperpolarization experiments, promising approaches to access the hidden orders of magnitude of MR signals. pH(2) production on-site in medical research centers is vital for the proliferation of these technologies in the life sciences. However, previously suggested designs do not meet our requirements for safety or production performance (flow rate, pressure or enrichment). In this article, we present the safety concept, design and install… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
127
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(142 citation statements)
references
References 37 publications
(72 reference statements)
1
127
1
9
Order By: Relevance
“…Although up to now SABRE feasibility has been shown for a limited number of substrates and complexes it is potentially a very general technique because SABRE, unlike the conventional PHIP method, does not require a hydrogenative chemical reaction. Therefore, firstly, SABRE can potentially be expanded to a broad range of substrates and, secondly, by using SABRE one can continuously generate hyperpolarized signals with strong signal enhancement for protons [17][18][19] as well as for heteronuclei, e.g. 13 C and 15 N [8, 12, 13, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Although up to now SABRE feasibility has been shown for a limited number of substrates and complexes it is potentially a very general technique because SABRE, unlike the conventional PHIP method, does not require a hydrogenative chemical reaction. Therefore, firstly, SABRE can potentially be expanded to a broad range of substrates and, secondly, by using SABRE one can continuously generate hyperpolarized signals with strong signal enhancement for protons [17][18][19] as well as for heteronuclei, e.g. 13 C and 15 N [8, 12, 13, 20].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the conversion profile followed an exponential function with a time constant of around 846 min. Hövener et al 16 observed a similar profile in a borosilicate glass vial monitored over 41 h, again using NMR to determine the pH 2 fraction; they reported a similar time constant of around 820 min.…”
Section: In-situ Monitoring Of the Conversion Of Ph 2 In Nmr Tubesmentioning
confidence: 72%
“…15,16,21,27 The sample was placed in a bench-top NMR spectrometer (Magritek Spinsolve) operating at a 1 H Larmor frequency of 43.5 MHz. A spectrum was recorded using a standard 90…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, PHIP is a relatively inexpensive technique compared to DNP and SEOP, with the main costs arising from the need to produce para-H 2 by cryo-cooling. 10,11 …”
mentioning
confidence: 99%